Music in Mood Regulation and Coping Orientations in Response to COVID-19 Lockdown Measures Within the United Kingdom - Henry, Noah; Kayser, Diana; Egermann, Hauke (Frontiers in Psychology, 2021)
Music is a tool used in daily life in order to mitigate negative and enhance positive emotions. Listeners may orientate their engagement with music around its ability to facilitate particular emotional responses and to subsequently regulate mood. Existing scales have aimed to gauge both individual coping orientations in response to stress, as well as individual use of music for the purposes of mood regulation. This study utilised pre-validated scales through an online survey (N = 233) in order to measure coping orientations and music in mood regulation in response to the lockdown measures imposed in the United Kingdom as a consequence of the COVID-19 pandemic. Whilst the existing theoretical structure of the COPE model has indicated a poor fit for clustered coping orientations, a subsequent five-factor structure was determined for coping orientations in response to lockdown. Analyses include observations that positive reframing and active coping were predictors of music use in mood regulation amongst listener’s coping strategies. Higher use of music in mood regulation according to time spent listening and employment status during lockdown was observed; with furloughed and unemployed statuses showing higher use of music mood regulation than more stable employment statuses such as those that are employed full-time or retired. These results provide insight into how individuals have engaged with music orientated coping strategies in response to a unique stressor.